Sharp teeth or empty mouths? Revisiting the minimum wage bite with sectoral data - Garnero, Andrea; Kampelmann, Stephan; Rycx, François (Bonn, 2013)
"The paper explores the link between different institutional features of minimum wage systems and the minimum wage bite. We notably address the striking absence of studies on sectorallevel minima and exploit unique data covering 17 European countries and information from more than 1100 collective bargaining agreements. Results provide evidence for a neglected trade-off: systems with bargained sectoral-level minima are associated with higher Kaitz indices than systems with statutory floors, but also with more individuals actually paid below prevailing minima. Higher collective bargaining coverage can to some extent reduce this tradeoff between sharp teeth (high wage floors) and empty mouths (noncompliance/noncoverage)."